Father Involvement of Circular Migrant Worker: The Role of Paternal Self-Efficacy and Mother Social Support - Zahira, Dhia; Alfiasari (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
Fathering plays a very important role in child development. Circular migrant worker fathers who live in different regions from their families will have many difficulties to carry out the parenting role. The purpose of this study is to analyze the influence of paternal self-efficacy and mother support on father involvement in circular migrant workers. This study used a quantitative approach with an explanatory research design. The sampling technique used was snowball sampling and data collection was done online using Google Form with a total respondent of 41 circular migrant worker fathers. The data was processed using Microsoft Office Excel and analyzed using SPSS. The results showed that the father's age was significant positively correlated with paternal self-efficacy, while paternal self-efficacy, mother support, and father involvement have a significant positive relationship with each other. The education level of father has significant negative relationship with paternal self-efficacy and mother support. The result of regression test showed that education level of father has a significant negative influence on father involvement. Furthermore, paternal self-efficacy and mother support has a significant positive influence on father involvement of circular migrant worker. The findings in this study emphasize the need to take sides with the protection of parent-child relationships in families that are structurally separate, such as families of circular migrant workers.